2013
DOI: 10.1680/macr.13.00053
|View full text |Cite
|
Sign up to set email alerts
|

Size effect on compressive behaviours of normal-strength concrete cubes made from demolished concrete blocks and fresh concrete

Abstract: This work presented in this paper contributes to a comprehensive research into structural elements containing demolished concrete blocks (DCBs) with a distinctly larger size than conventional recycled aggregates. In this research, 51 cubic specimens made from DCBs and fresh concrete (FC) with a replacement ratio of 30% were fabricated and tested under uniaxial compressive loadings. Two parameters were considered -the cube dimension and the characteristic size of DCBs. The influence of the two factors on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 15 publications
4
15
0
Order By: Relevance
“…After that, core concrete of the waste components was broken into blocks by using simple tools such as pneumatic picks and hammers. Based on the experimental studies and actual practices conducted by the authors in the past six years [22][23][24][25][26][27], it is suggested that the best ratio of the characteristic size of DCBs to the short side of the specimen's (or structural member's) cross section ranges from 1/3 to 1/2, to ensure the casting quality of DCBs and FC combined concrete. In this way, the characteristic size of the broken DCBs was mainly ranging from 100 mm to 150 mm in this study (Fig.…”
Section: Specimen Designmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, core concrete of the waste components was broken into blocks by using simple tools such as pneumatic picks and hammers. Based on the experimental studies and actual practices conducted by the authors in the past six years [22][23][24][25][26][27], it is suggested that the best ratio of the characteristic size of DCBs to the short side of the specimen's (or structural member's) cross section ranges from 1/3 to 1/2, to ensure the casting quality of DCBs and FC combined concrete. In this way, the characteristic size of the broken DCBs was mainly ranging from 100 mm to 150 mm in this study (Fig.…”
Section: Specimen Designmentioning
confidence: 99%
“…At present, a large amount of waste concrete still ends up at disposal sites. In order to explore a more efficient approach to reuse the waste concrete directly as an acceptable structural material, some new kinds of structural members containing both fresh concrete (FC) and broken demolished concrete with distinctly larger size than conventional recycled aggregates (usually with a size of 640 mm) were proposed and investigated by the authors [22][23][24][25][26][27]. Here the term of ''broken demolished concrete'' refers to the demolished concrete blocks (DCBs, usually with a size of 100-300 mm) or demolished concrete segments (DCSs, usually with a size of >500 mm in length).…”
Section: Introductionmentioning
confidence: 99%
“…
Contribution by J. R. Martí-VargasBased on interest in using demolished concrete blocks (DCBs), the paper by Wu et al (2013) presents research on the uniaxial behaviours of cubic concrete specimens. The authors should be complimented for producing this detailed paper of interest for the discusser, who would like to offer some comments for the authors' consideration and response, mainly about the size effect on concrete compressive strength and concrete modulus of elasticity.

Regarding the effect of cube dimension on compressive strength, the authors found that compressive strength decreases if the cube dimension increases when DCBs are used.

…”
mentioning
confidence: 99%
“…A series of experimental studies on structural members (beams, columns, slabs, and walls) containing DCLs have now been carried out to examine the feasibility of such recycling [26][27][28][29][30][31][32]. Test results show that the mechanical properties and seismic performance of structural members containing DCLs are similar to or only slightly lower than those of such members containing FC alone.…”
Section: Introductionmentioning
confidence: 99%